Case Series On Acute Kidney Injury In Patients With Rift Valley Fever At Mbarara Regional Referral Hospital, Southwestern Uganda - Rose Muhindo; Grace Kansiime; Badru Kayongo; Abel Mwine; Gerald Atukwase; Simon Ahimbisibwe; Musa Kitandwe; Christopher Mugabo; Ernest Ssewanyana; Silver Atuzarirwe; Oswald Katsigire; Nicholas Nuwashaba; et al. (Journal of Medical Case Reports and Case Series, 2025)
Introduction: Rift Valley Fever (RVF) is an endemic zoonotic viral disease which usually affects livestock in parts of Africa and the Middle East. In patients infected with RVF, there is a risk of acute kidney injury (AKI) and acute liver failure (ALF). In this report, we present a case series of four patients diagnosed with RVF infection, highlighting the complications of AKI and ALF, with varying outcomes, including the utilization and impact of dialysis. Methods: We conducted a retrospective analysis of medical records for four patients admitted and managed at Mbarara Regional Referral Hospital (MRRH) in Southwestern Uganda with confirmed Rift Valley Fever infection. Clinical, laboratory, and outcome data were collected and summarized. Results: All four patients presented with characteristic symptoms suggestive of RVF, and laboratory investigations confirmed the diagnosis. Each patient had complications of AKI and acute liver failure. All patients required dialysis for renal support; however, logistical issues prevented access to hemodialysis for all but two of the patients. Among the patients who received hemodialysis, both demonstrated recovery from AKI. Unfortunately, the two patients who were unable to access dialysis succumbed to the complications. Conclusion: RVF infection can lead to severe complications, including AKI and acute liver failure. The timely initiation of dialysis appears crucial for improved outcomes in these cases. However, logistical barriers may hinder access to dialysis, emphasizing the need for improved healthcare infrastructure and accessibility in regions endemic to RVF.
Keywords: Rift Valley Fever; Acute Kidney Injury; Acute Liver Failure